Dental peculiarities in the silvery mole-rat: an original model for studying the evolutionary and biological origins of continuous dental generation in mammals - Gomes Rodrigues, Helder; Šumbera, Radim (PeerJ, 2015)
Unravelling the evolutionary and developmental mechanisms that have impacted the mammalian dentition, since more than 200 Ma, is an intricate issue. Interestingly, a few mammal species, including the silvery mole-rat Heliophobius argenteocinereus, are able to replace their dentition by the addition of supernumerary molars at the back of jaw migrating then toward the front. The aim here was to demonstrate the potential interest of further studying this rodent in order to better understand the origins of continuous dental replacement in mammals, which could also provide interesting data concerning the evolution of limited dental generation occurring in first mammals. In the present study, we described the main stages of the dental eruptive sequence in the silvery mole-rat and the associated characteristics of horizontal replacement using X-ray microtomography. This was coupled to the investigation of other African mole-rats which have no dental replacement. This method permitted to establish evidence that the initial development of the dentition in Heliophobius is comparable to what it is observed in most of African mole-rats. This rodent first has premolars, but then identical additional molars, a mechanism convergent to manatees and the pygmy rock-wallaby. Evidence of continuous replacement and strong dental dynamics were also illustrated in Heliophobius, and stressed the need to deeply investigate these aspects for evolutionary, functional and developmental purposes. We also noticed that two groups of extinct non-mammalian synapsids convergently acquired this dental mechanism, but in a way differing from extant mammals. The discussion on the diverse evolutionary origins of horizontal dental replacement put emphasis on the necessity of focusing on biological parameters potentially involved in both continuous and limited developments of teeth in mammals. In that context, the silvery mole-rat could appear as the most appropriate candidate to do so.
Keywords: Bathyergidae; Teeth; Morphology; Bone remodelling; Replacement; Drift; Resorption; Synapsids